The Influence of Teachers’ Skills in Applying Teaching Variations on Learning Motivation in Fiqh Subjects among Tenth Grade Students at MA Swasta Al-Maksum Stabat - Muhammad Akbar Thoha; Dedi Masri; Muhammad Rapono (CV PUTRA PUBLISHER, 2026)
One of the important skills that had to be mastered by teachers was the ability to apply teaching variations, because a lack of this skill often created problems during the learning process. This study aimed to determine the Fiqh teachers’ skills in applying teaching variations, students’ learning motivation in Fiqh subjects, and the influence of teachers’ teaching variation skills on students’ learning motivation at MAS Al-Maksum. This study used a quantitative research method. The population consisted of all students of MAS Al-Maksum, totaling 130 students, while the sample included 26 students. The research variables were teachers’ skills in applying teaching variations (X) and students’ learning motivation (Y). Data were analyzed using the product moment correlation formula. The findings showed that there was a significant relationship between teachers’ skills in applying teaching variations and students’ learning motivation. The statistical analysis indicated that the correlation coefficient value was r_xy = 0.40, which was categorized as a high correlation. In addition, the calculation result showed that t_count was higher than t_table at the 5% significance level (2.149 > 1.71). The percentage of teachers’ skills in applying teaching variations reached 76.29%, while students’ learning motivation reached 84.13%. These findings indicated that teachers’ skills in applying teaching variations influenced students’ learning motivation by 16%. Therefore, the use of varied teaching methods played an important role in increasing students’ motivation to learn Fiqh subjects.